2020
DOI: 10.1371/journal.pgen.1009017
|View full text |Cite
|
Sign up to set email alerts
|

ZNF423 patient variants, truncations, and in-frame deletions in mice define an allele-dependent range of midline brain abnormalities

Abstract: Interpreting rare variants remains a challenge in personal genomics, especially for disorders with several causal genes and for genes that cause multiple disorders. ZNF423 encodes a transcriptional regulatory protein that intersects several developmental pathways. ZNF423 has been implicated in rare neurodevelopmental disorders, consistent with midline brain defects in Zfp423-mutant mice, but pathogenic potential of most patient variants remains uncertain. We engineered~50 patient-derived and small deletion var… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Studies have shown that MSUT2 knockout has anti-inflammatory and neuroprotective effects in a mouse model. The flowchart is Frankel et al, 1987;Wolfe et al, 2000;Schefe et al, 2006;Brayer et al, 2008;Town et al, 2009;Fan et al, 2012;Shi et al, 2013;Yuan et al, 2013;Xu et al, 2016;Yu et al, 2017;Brahmachari et al, 2019;Kruszka et al, 2019;Lorsch et al, 2019;Ohkubo et al, 2019;Zhang et al, 2019;Choi et al, 2020;Deshpande et al, 2020;Hu et al, 2020;Xiao et al, 2020;Dentici et shown in Figure 1. Loss of function of MSUT2 can reduce the formation of tau protein and protect the loss of neurons, but the molecular mechanism is still unclear.…”
Section: Alzheimermentioning
confidence: 99%
“…Studies have shown that MSUT2 knockout has anti-inflammatory and neuroprotective effects in a mouse model. The flowchart is Frankel et al, 1987;Wolfe et al, 2000;Schefe et al, 2006;Brayer et al, 2008;Town et al, 2009;Fan et al, 2012;Shi et al, 2013;Yuan et al, 2013;Xu et al, 2016;Yu et al, 2017;Brahmachari et al, 2019;Kruszka et al, 2019;Lorsch et al, 2019;Ohkubo et al, 2019;Zhang et al, 2019;Choi et al, 2020;Deshpande et al, 2020;Hu et al, 2020;Xiao et al, 2020;Dentici et shown in Figure 1. Loss of function of MSUT2 can reduce the formation of tau protein and protect the loss of neurons, but the molecular mechanism is still unclear.…”
Section: Alzheimermentioning
confidence: 99%
“…In addition to defects in the SCPs, the MTS is due to an underdeveloped cerebellar vermis, so we examined the size of the cerebellum and the cerebellar vermis (Figure 5) (Aguilar et al 2012). To quantify cerebellar size, we performed analysis of surface-facing anatomical measurements validated to be sufficiently sensitive to detect small differences in cerebellar vermis size (Deshpande et al 2020). Briefly, we measured cerebellar width as well as cerebellar vermis width (widest part of lobule VII) of fixed whole mount dissected brains.…”
Section: Resultsmentioning
confidence: 99%
“…Weanling age (P20-P24) male and female mice were sacrificed and brains were harvested and fixed in 4% PFA overnight at 4⁰. Ten sex-matched pairs of mouse brains were collected for each genotype, which is sufficiently powered to detect differences as small as 3% (Deshpande et al 2020). Brains were imaged on a tilted stage to present a surface view of the cerebellum, with a standard ruler in frame to confirm scale, using a dissecting microscope (Leica MZFLIII).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations